Prognostic role of in vitro survival efficiency in human transitional- cell carcinoma - (:unkn) unknown (My University, 1999)
The purpose of this study was to assess the correlation of in vitro growth features of transitional-cell carcinoma (TCC) specimens with the clinical behavior of the respective tumors. We also analyzed the impact of depth of tumor invasion, histologic differentiation, morphologic characteristics, and nuclear p53 accumulation of tumors on the in vitro survival efficiency of microtumor cultures and the significance of these factors in predicting recurrence and progression of bladder cancer. The tumor cell lines derived from surgical specimens were cultured at 37°C in 5% CO2 and constant humidity. Microtumor cultures were classified into three groups according to their in vitro lifespan. Our results indicate that higher survival efficiency implies a propensity for aggressive clinical behavior of the tumor in vivo. Factors that imply a poorer prognosis account for longer lifespans for microtumour cultures. These prognostic indicators are also associated with higher rates of recurrence and progression for tumors that exhibit higher survival efficiency in vitro.